Joint Effusion Workshop - Beth Rubinstein; Faizah Siddique (Association of American Medical Colleges, 2016)
Abstract Introduction The purpose of this workshop is to create an interactive working model for diagnosis and management of a patient with a joint effusion. The workshop has been formatted to reflect how a medical student would encounter a patient during clinical rotations. Methods After a case presentation, each student, independently and in a small group, must demonstrate his/her ability to ask appropriate history-taking and physical exam skills in order to create a differential diagnosis for a joint effusion. After creating a thorough differential diagnosis, the students are asked to review different synovial fluid analyses, with a focus on cell count and differential, culture, and crystal identification. Finally, the unit concludes with a discussion of the management of common crystal-induced arthritides and septic arthritis. The recognition of a swollen and inflamed joint is crucial in the diagnosis and management of a joint effusion. Prompt diagnosis of a septic joint can lower the risk of significant morbidity and mortality. Results The workshop has been successfully used for 3 years at Virginia Commonwealth University. Feedback has been positive, and the session qualifies as an active, or engaged, learning opportunity for students. One example of feedback is as follows: "The joint effusion workshop was great! It was really good that we walked through a case after having been able to study the information and then we could see it come together." Discussion This workshop prepares students to be able to recognize and clinically manage a joint effusion. These are skills that will serve them well during the remainder of their clinical careers.